Role of cell surface proteins and toll-like receptors in the pathogenesis of Streptococcus pneumoniae - Anuar, Nurul Fathiyah Zaipul; Desa, Mohd Nasir Mohd; Hussaini, Jamal; Wong, Eng Hwa; Mariappan, Vanitha; Vellasamy, Kumutha Malar; Palanisamy, Navindra Kumari (Mashhad University of Medical Sciences, 2024)
Objective(s): Pneumococcal cell wall (PCW) is an inflammatory component in Streptococcus pneumoniae. The cell surface proteins and the toll-like receptors (TLR) signaling response were investigated in the human lung epithelial (A549) cells inoculated with PCW of different serotypes. Materials and Methods: The presence of genes encoding these proteins was determined using polymerase chain reaction (PCR). The structure of the cell walls was analyzed by proton nuclear magnetic resonance (1H NMR). The A549 cell line was challenged with PCW extracts of different serotypes. RNA from the infected host cells was extracted and tested against a total of 84 genes associated with TLR signaling pathways (TLR 1-6 and 10) using RT2 Profiler PCR Array. Results: Cell surface proteins; ply, lytA, nanA, nanB, and cbpD genes were present in all serotypes. The distribution and structure of surface protein genes suggest behavioral changes in the molecules, contributing to the resilience of the strains to antibiotic treatment. Conclusion: TLR2 showed the highest expression, while serotypes 1, 3, and 5 induced higher TNFα and IL-1α, suggesting to be more immunogenic than the other strains tested. © 2024 Mashhad University of Medical Sciences. All rights reserved.